Effects of Varying Diagnostic Coverage on Functional Safety - Ustoglu, Ilker; Kaymakci, Ozgur T.; Boercsoek, Josef (IEEE, 2014)
Diagnostics is one of the significant parameters of functional safety which concerns itself with revealing dangerous incidents that might impede the operation of safety systems. Diagnostic coverage factor (DC) is defined as a metric for diagnostics in that DC is one of the most important design parameters to measure the effectiveness of safety protection systems. This study addresses how diagnostics impacts proof test interval (T-I) when the system is halted completely; a thorough maintenance and changes in parts are performed. Besides this, the relationship between average probability of failure on demand (PFDavg), DC, T-I and mean time to failure (MTTF) are presented for 1oo2 and 1oo2D system architectures.
Keywords: Diagnostic coverage factor; mean time to failure; probability of failure on demand; safety architecture; Engineering